Green Synthesis of ZnO Nanoparticles using Nigella sativa Seeds Aqueous Extract and Antibacterial Activity Evaluation - Fawaz Al-Badaii, Fawaz Al-Badaii; Halim, Azhar Abdul; Alsharabi, Amal; Altiby, Ebtesam; Naji, Entsar; Mahdi, Kholod; Hujerh, Mona; Alshawkani, Nabilah; Alshamy, Rehab; Alsayouri, Walid (International Journal of Scientific Research in Biological Sciences, 2023)
This study aimed to determine the antimicrobial activity of ZnONPs synthesized by the green method using Nigella sativa extract against Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Streptococcus pyogenes. In addition, the effect of pure ZnONPs on the same bacteria was compared to the effect of ZnONPs synthesized using the green method. The synthesis of ZnONPs was carried out using the standard green method. The results indicate that ZnONPs synthesized by N. sativa seed extract had an effect against S. aureus with a zone of 19 mm obtained from the concentration of 150 mg/ml of ZnONPs synthesized using 25 ml of N. sativa seed extract. Also, ZnONPs showed antimicrobial activity against S. pyogenes in zone 19 mm at 150 mg/ml concentrations of ZnONPs synthesized using 25 ml of N. sativa. The synthesized ZnONPs showed activity against K. pneumoniae in zone 14 mm for 100 mg/ml and 150 mg/ml of ZnONPs synthesized using 25 ml of N. sativa extract. Moreover, ZnONPs synthesized by the green method was low effective on P. aeruginosa. Finally, the results exhibited low antimicrobial activity of pure ZnONPs compared to the ZnONPs synthesized by the green method, and the best effect of ZnONPs was obtained at concentrations of 150 mg/ml of ZnONPs synthesized from 25 ml of N. sativa extract.